2006
DOI: 10.1084/jem.20052450
|View full text |Cite
|
Sign up to set email alerts
|

Malaria infection changes the ability of splenic dendritic cell populations to stimulate antigen-specific T cells

Abstract: The capacity of splenic CD11c+ dendritic cell (DC) populations to present antigen (Ag) to T cells differs during malarial infection with Plasmodium chabaudi in mice. Both CD11c+CD8+ and CD8− DCs presented malarial peptides on their surface during infection. However, although both DC subsets expressing malaria peptides could induce interferon-γ production by CD4 T cells, only CD8− DCs isolated at the acute phase of infection stimulated Ag-specific T cell proliferation and interleukin (IL)-4 and -10 production f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
159
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(176 citation statements)
references
References 28 publications
15
159
1
1
Order By: Relevance
“…It is likely that such T-cell help will support switching to a range of Ig isotypes in anti-malaria Ab responses. Previous studies in mice, and in vitro for human cells, have shown DC to be inhibited from priming T cells in the presence of malarial parasites [15,26,27], but this phenomenon was not seen here.…”
Section: Discussioncontrasting
confidence: 63%
“…It is likely that such T-cell help will support switching to a range of Ig isotypes in anti-malaria Ab responses. Previous studies in mice, and in vitro for human cells, have shown DC to be inhibited from priming T cells in the presence of malarial parasites [15,26,27], but this phenomenon was not seen here.…”
Section: Discussioncontrasting
confidence: 63%
“…A similar result was obtained when CD8 + DC were depleted in P. chabaudi-infected mice (38). Another study analyzing CD4 + T cell responses to P. chabaudi Ag showed CD8 + DC as superior to CD8 2 DC at MHC II presentation in the steady-state, but the latter were more efficient during infection (39). In the P. chabaudi model, mice devoid of CD8 + DC developed higher peaks of parasitemia and more pronounced relapses than did their WT counterparts (40).…”
supporting
confidence: 59%
“…Previous reports using DC from infected mice ex vivo have implicated both CD8 + and CD8 2 DC in MHC II-restricted Ag presentation during blood-stage malaria infection (9,39,63). To examine the capacity of cDC subsets to present malaria Ags to CD4 + T cells, we enriched cDC (defined as CD11c hi MHC II hi cells) from the spleens of naive mice and subdivided them into three subsets: CD8 + CD4 2 , CD8 2 CD4 + , and CD8 2 CD4 2 DC (CD8 + , CD4 + , and DN DC, respectively) (64).…”
Section: Cd8 + DC Are the Main Apc For Pbt-ii Cellsmentioning
confidence: 99%
“…The advantage of stromal cell plasticity to the organism is that it provides a mechanism able to meet the changing requirements for hematopoietic cells of a given lineage. In the context of infections, such as leishmaniasis (23,29,31), tuberculosis (46), and malaria (32,47), alterations in local stromal cells, as well as the enhanced capacity to support HSPC renewal and recruitment that promotes the differentiation of DCs and T cells with regulatory function, might be common host responses to several pathogens to prevent immune-mediated pathology, although also promoting pathogen persistence. Similarly, an accumulation of DCs and other myeloid cells with immune-suppressive functions has been noted in cancers associated with altered stromal cell function (48).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this infection also promotes the capacity of splenic stromal cells to support regulatory DC differentiation (23). Similar changes may also occur in experimental malaria infections (32). However, the precise cellular components and niche-derived factors allowing HSPC differentiation into regulatory DCs within various vascular niches at steady state and in the course of chronic infectious diseases remain unclear.…”
mentioning
confidence: 96%